2021
DOI: 10.3389/fonc.2020.618374
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Cancer Molecular Characterization of m6A Regulators and Immunogenomic Perspective on the Tumor Microenvironment

Abstract: PurposeN6-methyladenosine (m6A) methylation plays a critical role in diverse biological processes. However, knowledge regarding the constitution of m6A on tumor microenvironment (TME) and tumor-infiltrating lymphocytes (TILs) across cancer types is still lacking. We performed comprehensive immuno-genomic analyses to reveal molecular characterization of the m6A regulators and immune-related genes (IRGs) across TME and TIL heterogeneity.MethodsWe comprehensively analyzed the properties of m6A regulators in genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 56 publications
1
24
0
Order By: Relevance
“…Most of the anticancer immune regulations rely on overcoming the continuous suppression of the adaptive immune response within the TME ( 43 ). Immune suppression is a typical feature of the TME, which involves the dysfunction of antigen presenting cells (APCs), recruitment or induction of large numbers of suppressive immune cells, such as CD4+ regulatory T cells (Tregs), dendritic cells (DCs), tumor-associated macrophages (TAMs), and myeloid cell-derived suppressor cells (MDSCs), and secretion of various cytokines ( Figure 2 ) ( 44 , 45 ).…”
Section: A Modification As a Novel Regulator Of The Tumor Immune Microenvironmentmentioning
confidence: 99%
“…Most of the anticancer immune regulations rely on overcoming the continuous suppression of the adaptive immune response within the TME ( 43 ). Immune suppression is a typical feature of the TME, which involves the dysfunction of antigen presenting cells (APCs), recruitment or induction of large numbers of suppressive immune cells, such as CD4+ regulatory T cells (Tregs), dendritic cells (DCs), tumor-associated macrophages (TAMs), and myeloid cell-derived suppressor cells (MDSCs), and secretion of various cytokines ( Figure 2 ) ( 44 , 45 ).…”
Section: A Modification As a Novel Regulator Of The Tumor Immune Microenvironmentmentioning
confidence: 99%
“…The ssGSEA scores for most immune cell populations were obtained using the gene sets from Angelova et al (15). A total of 29 gene sets representing distinct immune cell populations were obtained: activated dendritic cells (aDCs), antigen-presenting cell (APC) co-inhibition, APC co-stimulation, B cells, CC chemokine receptor (CCR), CD8+ T cells, Checkpoint, Cytolytic activity, dendritic cells (DCs), human leukocyte antigen (HLA), interdigitating dendritic cells (iDCs), Inflammation-promoting, Macrophages, Mast cells, MHC class I, Neutrophils, NK cells, Parainflammation, plasmacytoid dendritic cells (pDCs), T cell-co-inhibition, T cell costimulation, T helper cells, follicular helper T cells (Tfh), Th1 cells, Th2 cells, tumor-infiltrating lymphocytes (TIL), regulatory T cells (Treg), Type I IFN Response, Type II IFN Response (16,17).…”
Section: Gene Enrichment Analysis and Tumor-infiltrating Cells Analysismentioning
confidence: 99%
“…TME components directly and indirectly affect multiple biological behaviors of cancer cells such as inhibiting apoptosis, inducing proliferation, avoiding hypoxia, inducing immune tolerance, et al ( Binnewies et al, 2018 ). The evidence suggests that m6A modification could build a TME favorable for the growth of cancer cells ( Zhu et al, 2021 ). For instance, Yi Jian et al found that ALKBH5 could promote the progression of OC in a simulated TME via NF-κB signaling ( Jiang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%